The composition of prostate core matrisome in vivo and in vitro unveiled by mass spectrometric analysis - Marjaana Ojalill; Pekka Rappu; Elina Siljamäki; Pekka Taimen; Peter Boström; Jyrki Heino (John Wiley and Sons Inc., 2022)
Background: The composition and organization of extracellular matrix (ECM) are important regulators of cell behavior. In particular in the prostate, this central role of the ECM is further stressed by the fact that several potential markers of prostate stem cells are matrix receptors.
Methods: We established 12 fibroblastic cell lines from cancerous and non‐cancerous areas of six prostates and allowed the cells to produce ECM under cell culture conditions. We also performed a proteome wide analysis of the ECM components by mass spectrometry. To study the in vitro activation of fibroblastic cells we compared the differences between the ECM produced in cell culture by six non‐cancerous‐tissue‐derived fibroblasts and the in vivo matrisome from the corresponding non‐cancerous tissue of prostate.
Results: Our results suggest that at tissue level the ECM is mainly produced by fibroblastic cells and that it contains standard collagen I fibrils and fibril‐associated proteins. Beaded‐filament forming collagen VI is also abundant and basement membranes potentially contain five laminin subtypes and collagens XV and XVIII. As the main finding, we also detected differences when in vivo and in vitro matrisomes were compared. Only 65 out of 206 proteins were found to be common for both in vivo and in vitro samples. Majority of the 55 proteins, which were solely detected in in vivo samples, were considered to be plasma derived. Eighty‐six proteins were solely found from in vitro fibroblast‐derived ECM, and most of them were related to matrix remodeling or growth factor action, proposing that the activation of fibroblasts in cell culture may remarkably modify their gene expression profile. Finally, in comparison to traditional 2D in vitro cell culture, the ECM composition of 3D spheroid culture was analyzed. The matrisome in spheroid culture did not resemble the in vivo ECM more closely than in monolayer culture.
Conclusions: Artificial activation of ECM remodeling seems to be a distinctive feature in in vitro models. In conclusion the constitution of ECM produced by prostate derived fibroblasts in vitro is similar, but not identical to the prostate ECM in vivo as shown here by mass spectrometric analysis.